DAMPAK PENGABAIAN HUKUM TAJWID TERHADAP PERGESERAN MAKNA AYAT - Syauqi Aulia Ramadhani; M. Ilmil Zawawi (Jurnal Penelitian Pendidikan Indonesia (JPPI), 2026)
This study examines the impact of neglecting tajwid rules on the shifting meaning of Qur'anic verses. The main objective is to analyze how errors in pronunciation influence semantic interpretation. This research employs a qualitative approach with a library research method, using relevant literature such as classical tajwid books and scientific journals. The findings indicate that errors in makhraj, vowel marks (harakat), and lengthening (mad) can significantly alter phonological structures, leading to changes in lexical and grammatical meaning. In some cases, these errors may even affect theological interpretation. The study concludes that tajwid is not merely a recitation technique but a fundamental linguistic system that preserves the authenticity of Qur'anic meaning.